miR-214-5p Regulating Differentiation of Intramuscular Preadipocytes in Goats via Targeting KLF12 - Du, Yu; Wang, Yong; Li, Yanyan; Emu, Quzhe; Zhu, Jiangjiang; Lin, Yaqiu (Frontiers in Genetics, 2021)
Abstract: Intramuscular fat (i.m.) is adipose tissue that deposited between muscle bundles. An important type of post-transcriptional regulatory factor, miRNAs, has been seemed as a important regulator that can regulate gene expression and cell differentiation through specific binding with target genes, which is the pivotal way determining intramuscular fat deposition. Thus, this study intends to use RT-PCR, cell culture, liposome transfection, real-time fluorescent quantitative PCR (qPCR), dual luciferase reporter system and other biological methods clarifying the possible mechanisms on goat intramuscular preadipocytes differentiation that regulated by miR-214-5p. Ultimately, our results showed that the expression level of miR-214-5p peaked at 48 h after the goat intramuscular preadipocytes were induced for adipogenesis. Furthermore, after inhibited the expression of miR-214-5p the accumulation of lipid droplets and adipocytes differentiation in goat intramuscular adipocytes were promoted by the way of up-regulated the expression level of Lipoprotein lipase (LPL) (P<0.05), Preoxisome proliferator-activated receptor gamma (PPARγ) (P<0.01) while inhibited the expression of Hormone-sensitive lipase (HSL) (P<0.01). Subsequently, our study confirmed that Krüppel-like factors 12 (KLF12) was the target gene of miR-214-5p. Inhibited the expression of KLF12 promoted adipocytes differentiation and lipid accumulation by up-regulated the expression of LPL and CCAAT/enhancer binding protein (C/EBPα) (P<0.01). Overall, these results indicated that miR-214-5p and its target gene KLF12 were negative regulators in progression of goat preadipocytes differentiation. Our research results provided an experimental basis for finally revealing the mechanism of miR-214-5p in adipocytes.